Development of a layered bacterial nanocellulose-PHBV composite for food packaging - Silva, Francisco Almeida Garrett Soares (2022)
Abstract BACKGROUND Most of the current materials used in food packaging are synthetic and non-degradable, raising environmental issues derived from the accumulation of plastics in landfills/waterways. The food industry increasingly needs eco-friendly sustainable materials that meet the food packaging requirements. Bacterial nanocellulose (BNC), a biopolymer obtained by fermentation, offers very good mechanical properties as well as the ability to carry and deliver active substances. However, its water vapour permeability is too high for food packaging applications. In this work, a layered biodegradable composite based on BNC and polyhydroxyalkanoates (PHBV) was produced, attempting to improve the overall barrier properties. PHBV is a biopolymer with high degree of hydrophobicity and biodegradability, also obtained by fermentation. Wet BNC membranes produced by static culture were plasticized by impregnation of solutions of either glycerol (BNCgly) or polyethylene glycol (MW600) (BNCPEG). The plasticized BNC was then coated with PHBV solution dissolved in formic acid, and oven-dried at 148 °C. RESULTS Overall, PHBV coating on plasticized BNC reduced significantly the water vapour permeability (from 0.990 to 0.032g.m.m2.day1.Pa1) under 50% relative humidity. It increased the hydrophobicity (contact angle from 1040° to 8090°), but decreased the stiffness (from 3.1GPa to 1.3 Gpa) of the composite. CONCLUSIONS Overall, the mechanical and barrier properties of the obtained layered composite were considered suitable for food packaging applications. The plasticizing (with glycerol or polyethylene glycol) of BNC significantly improved the mechanical performance, while PHBV coating reduced the water affinity (vapour and liquid state) on BNC.